Aerobic respiration, biochemical composition, and glycolytic responses to ultraviolet radiation in jellyfish Cassiopea sp - Aljbour, Samir M.; Alves, Ricardo N.; Agustí, Susana (Frontiers in Marine Science, 2023)
The light-dependent zooxanthellate jellyfish Cassiopea sp. (the upside-down jellyfish) is invasive/exotic in many shallow and clear marine habitats, where the jellyfish might be exposed to high levels of ultraviolet radiation (UVR). Compared to other reef organisms, the sensitivity/resilience of the semi-transparent jellyfish to UVR exposure is overlooked. Therefore, we experimentally investigated the metabolic and physiological responses of Cassiopea sp. from the Red Sea to natural levels of underwater UVR following 16 days of exposure to three light treatments: 1) control group with only photosynthetically active radiation (PAR), 2) PAR+UV-B, and 3) PAR+UV-B+UV-A. While jellyfish body mass increased (by 40%) significantly in the control group, it did not increase in either of the UV treatments. However, both UV-exposed jellyfish had higher (98% to 120%) mitochondrial electron transport system (ETS) activity than the control group. Therefore, the results indicate elevated aerobic respiration rates in UV-exposed jellyfish (i.e., reflecting a higher energy cost of UVR exposure). Neither the lactate dehydrogenase (LDH) activity nor the available energy (Ea) exhibited different levels among UVR treatments compared to the control group. In contrast, pyruvate kinase activity was significantly lower (by 46%) in all UV-exposed jellyfish compared to the control group. Unchanged Ea and LDH activity combined with higher ETS activity indicates a high aerobic capacity of jellyfish, which might explain their ability to cope with UVR exposure-induced higher energy demands without inducing the onset of anaerobiosis. The results indicated that UV-A does not amplify or modulate jellyfish physiology and growth under UV-B exposure. In conclusion, the findings suggest that the jellyfish is more resilient (i.e., in terms of survival) to UVR than other cnidarians. This study on Cassiopea is the first to address its metabolic and physiological responses to UVR. Therefore, it could be used as a framework for further studies aiming to better understand jellyfish physiology.